2011
DOI: 10.1177/156482651103200305
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prophylactic Iron Supplementation in Healthy Pregnant Women on Maternal Iron Status and Birth Outcome

Abstract: Background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(74 citation statements)
references
References 18 publications
1
70
1
2
Order By: Relevance
“…32 Under conditions of adequate iron status, hemoglobin levels should remain relatively stable, as absorbed iron is stored in ferritin, rather than used in hemoglobin production. This reasoning is supported by intervention studies conducted in infants 9 and pregnant women 33 , which found no difference in hemoglobin concentrations following supplementation among non-iron-deficient individuals Although there is limited literature on the relation of hemoglobin status with height in iron-replete populations, a recent cohort study conducted in non-iron-deficient Italian infants provided no evidence of a clear association between hemoglobin status and length gain between 6 and 24 months. 7 Our study has several strengths.…”
Section: Discussionmentioning
confidence: 99%
“…32 Under conditions of adequate iron status, hemoglobin levels should remain relatively stable, as absorbed iron is stored in ferritin, rather than used in hemoglobin production. This reasoning is supported by intervention studies conducted in infants 9 and pregnant women 33 , which found no difference in hemoglobin concentrations following supplementation among non-iron-deficient individuals Although there is limited literature on the relation of hemoglobin status with height in iron-replete populations, a recent cohort study conducted in non-iron-deficient Italian infants provided no evidence of a clear association between hemoglobin status and length gain between 6 and 24 months. 7 Our study has several strengths.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Siega‐Riz et al reported that 65% of the population in their placebo group were iron deficient and 15% had IDA (defined as hemoglobin <11.0 g/dL and serum ferritin <20 μg/L). Falahi et al also reported an NAID rate of 28% in their non‐supplemented study population .…”
Section: Resultsmentioning
confidence: 84%
“…All of the studies examining oral iron supplementation in non‐anemic women reported neonatal outcomes and in two of them, there were significant improvements in birthweight seen with oral iron supplementation .…”
Section: Resultsmentioning
confidence: 99%
“…The effect of iron supplementation has been found dose (more than 91 mg/day) along with duration (11 -13 weeks) dependent. With 60 mg of iron (ferrous sulfate)/day, Falahi et al [21], in Iran, got a significant difference of hemoglobin and ferritin rates between supplemented women and placebos. Nevertheless, a daily supplement of 30 -40 mg iron during the third trimester has been suggested as adequate to maintain satisfactory hematological status during pregnancy [15] [22].…”
Section: Discussionmentioning
confidence: 99%